2020
DOI: 10.4103/jiaps.jiaps_166_18
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor expression in hypospadias

Abstract: Introduction:The exact mechanism behind the development of hypospadias is unclear. Research studies on androgen receptor (AR) expression are controversial with results stating all possible outcomes – AR elevated, similar, or reduced when compared to normal.Aims:The aim is to study the AR expression and hormone levels in hypospadias patients and compare them with children having normal genitalia.Methods:Group 1 (controls) involved patients who underwent circumcision for phimosis while Group 2 involved hypospadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…If these symptoms do occur, the foreskin can be repeatedly pulled back to dilate the foreskin mouth. By doing so, and with passage of time, most cases of phimosis in children can be cured, and only a small number of children need circumcision or cerclage surgery[ 11 ]. Although circumcision is a minor surgery, patients who receive this surgery tend to hold high expectations for it.…”
Section: Discussionmentioning
confidence: 99%
“…If these symptoms do occur, the foreskin can be repeatedly pulled back to dilate the foreskin mouth. By doing so, and with passage of time, most cases of phimosis in children can be cured, and only a small number of children need circumcision or cerclage surgery[ 11 ]. Although circumcision is a minor surgery, patients who receive this surgery tend to hold high expectations for it.…”
Section: Discussionmentioning
confidence: 99%
“…The human AR gene, also known as the dihydrotestosterone receptor, is located on X-chromosome and a member of the nuclear hormone receptor family. Although AR defect may play a causative role during the development of hypospadias, the AR expression (Balaji et al, 2020;Celayir et al, 2019;Lin et al, 2016;Pichler et al, 2013;Silva et al, 2013;Tack et al, 2019) in hypospadias is still debatable. Lin et al (2016) and Silva et al (2013) reported the decreased AR expression in boys with hypospadias compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…While any defect in the androgen signaling may lead to hypospadias, the AR expression in hypospadias are controversial with the variable results. When compared to the non‐hypospadiac children, AR expression exhibited various levels, including elevated (Balaji et al., 2020; Pichler et al., 2013), similar (Celayir, Moralioglu, Cetiner, Kir, & Celayir, 2019; Tack et al., 2019) or decreased (Lin, Xie, Chen, & Li, 2016; Silva et al., 2013). Various polymorphisms in ESR1 are associated with the risk of hypospadias (Choudhry et al., 2015), and ESR1 expression are also reported to be associated with hypospadias (Qiao et al., 2012; Wang et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balaji et al 12 analyzed AR expression in 16 hypospadias. This prospective study included 27 children with normal genitalia (who underwent circumcision for phimosis Group 1), and 16 hypospadias patients, with bilateral descended testis, and who had not received any preoperative testosterone (Group 2).…”
Section: Introductionmentioning
confidence: 99%